2014
DOI: 10.4269/ajtmh.13-0053
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Three Different Regimens of Primaquine for the Prevention of Relapses of Plasmodium vivax Malaria in the Amazon Basin of Peru

Abstract: Abstract. We evaluated the efficacy of three primaquine (PQ) regimes to prevent relapses with Plasmodium vivax through an open-label randomized trial in Loreto, Peru. Vivax monoinfections were treated with chloroquine for 3 days and PQ in three different regimes: 0.5 mg/kg per day for 5 days (150 mg total), 0.5 mg/kg per day for 7 days (210 mg total), or 0.25 mg/kg per day for 14 days (210 mg total). Biweekly fever assessments and bimonthly thick smears were taken for 210 days. Recurrences after 35 days were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 38 publications
2
59
2
Order By: Relevance
“…Moreover, it is highly unlikely that these recurrences were recrudescence by therapeutic failure to CQ since all participants had a negative PCR for malaria on day 28 posttreatment. Results from similar studies in other parts of the world reported a cumulative incidence of recurrence between 0% and 13.5% after treatment with 0.25 mg/kg/day PQ for 14 days and a follow-up time between 180 and 210 days, which is much lower than what was found in this study (38)(39)(40)(41)(42)(43).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Moreover, it is highly unlikely that these recurrences were recrudescence by therapeutic failure to CQ since all participants had a negative PCR for malaria on day 28 posttreatment. Results from similar studies in other parts of the world reported a cumulative incidence of recurrence between 0% and 13.5% after treatment with 0.25 mg/kg/day PQ for 14 days and a follow-up time between 180 and 210 days, which is much lower than what was found in this study (38)(39)(40)(41)(42)(43).…”
Section: Discussioncontrasting
confidence: 55%
“…This percentage is higher than that reported in other studies that used the same PQ supervised regimen and similar length of follow-up and genotyping approach for recurrences (microsatellite loci) (37,40). Additionally, 62.1% of recurrences were classified as relapses according to established criteria based on estimation of the P match within each genetic cluster, which could indicate a problem with efficacy of the PQ regimen used.…”
Section: Discussioncontrasting
confidence: 49%
“…18 Our findings show that P. vivax antimalarial regimen in Cruzeiro do Sul is highly efficacious for the acute phase of the infection, but is associated with moderate recurrent infection rates, mostly relapses, compared with a similar study in Peru. 19 In addition, we noted very good tolerance and rapid parasite clearance with the current firstline treatment of uncomplicated P. vivax malaria in Brazil.…”
Section: Discussionmentioning
confidence: 73%
“…The median total dose of chloroquine was 23.7 mg/kg (range = 15.0-35.7). 19 were lost to follow up, and seven had P. falciparum infection. Figure 2 shows day of recurrent episodes, either by P. vivax or P. falciparum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation